1999
DOI: 10.1136/thx.54.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity from asthma in relation to regular treatment: a community based study

Abstract: Background-The extent to which asthma morbidity in the community occurs in patients who are having relatively little treatment or in those on step 3 or above of the British asthma management guidelines is uncertain. We have looked at this in a community population in southern Nottinghamshire. Methods-A cross sectional review of treatment in all patients over the age of four with diagnosed asthma was carried out in five large general practices (population 38 865) in 1995/6 using computerised general practice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 10 publications
3
43
0
Order By: Relevance
“…It has been identified in 30% to 60% of patients, [4][5][6] and is associated with poor asthma control, 2 and increased mortality. 22 Although some studies have shown that patient education can improve adherence with inhaled corticosteroids, these interventions have been labour intensive, and their implementation has had limited success overall.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It has been identified in 30% to 60% of patients, [4][5][6] and is associated with poor asthma control, 2 and increased mortality. 22 Although some studies have shown that patient education can improve adherence with inhaled corticosteroids, these interventions have been labour intensive, and their implementation has had limited success overall.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…[4][5][6] Reasons for poor adherence are numerous, but include a dislike of inhaled corticosteroids, lack of rapid symptom relief, and complicated treatment regimens. [7][8][9] Because the β 2 -agonist formoterol has a rapid onset and long duration of action, 10 it can be used for symptom relief and maintenance treatment.…”
Section: Introductionmentioning
confidence: 99%
“…(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) In the attempt to improve asthma control, consensus guidelines including all of the relevant scientific information published have been systematically drawn up in various countries in order to aid health professionals in carrying out the treatment of these patients. However, the use of these guidelines by health professionals, in rich as well as in poor countries, have proven quite insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Reiterating this information both towards physicians and patients would therefore, seem very appropriate. Studies based on questionnaires as well as on general practice records indicate that physicians insufficiently prescribe maintenance treatment [18,19]. However, specific education programs increase both the prescription rate of and adherence to steroids, improving the overall degree of asthma control [9±11, 20].…”
mentioning
confidence: 99%